Performance evaluation and environmental impact assessment of systems with waste exergy emissions (2012)
The transformation and utilization of non-renewable energies involves irreversibility which makes our system less efficient. The environmental impact potential is equivalent to the work potential of the emissions.The irreversibility of inefficient systems has Global Warming Potential or environmental impact potential as wasted exergy is not always in equilibrium with the environment. Most literatures have either considered the optimization of thermodynamic systems for better efficiency or environmental effect of the transformation and utilization of energy separately. Focusing more on systems with waste emissions, the exergy lost to the environment through their waste emissions have environmental impact potential. This work reviews literatures on exergy analysis done for systems with waste emissions (heat and gaseous) and some literatures on environmental impact of human activities like gas flaring. The work further proposes more research into the development of a system that would integrate the environmental impact Potential into the calculation of exergetic efficiency of any thermodynamic system. This is to put researchers on their feet to come up with systems that will be exergy efficient and environmentally friendly. Exergy analysis being a good Environmental Impact Indicator can be used to both optimize our systems and also reduce the pollution of our environment.